Peluang Dan Tantangan Medical Tourism Perspektif Hukum Indonesia - Made Raditya Mahardika (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
, Currently medical tourism or commonly known as health tourism is becoming a trend in the world of tourism. The regulations regarding medical tourism in Indonesia were regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 76 of 2015 concerning Medical Tourism Services. The purpose of this paper is to examine the opportunities and challenges of medical tourism from an Indonesian legal perspective. The method for achieving this goal was normative legal research method. The results of the analysis showed that opportunities for medical tourism in the perspective of Indonesian law, namely Indonesian health regulations do not affect medical tourism behavior through health needs, external environment: government regulations on health tourism and health tourism agents, the implementation of medical tourism hospitals in Indonesia has not run optimally, PMK Number 76 of 2015 regarding Medical Tourism Services as a legal umbrella providing opportunities for medical tourism, plans to develop medical tourism in Indonesia are contained in Law No. 07 of 2017, and Pp No. 02 of 2015, simplification of medical tourism regulations (Perkonsil) No. 92 of 2021, PMK No. 67 of 2013, the medical tourism policy has been updated to empower medical tourism: KP No. 31 of 1998, Law No. 32 of 2004, PMK of the Republic of Indonesia Number 317/MENKES/PER/III/2010. The challenges of medical tourism from an Indonesian legal perspective: no legal accreditation framework and guidelines for emergency clinics, foreign investors must be aware that Indonesia has a series of regulations and restrictions relating to its health industry, the challenges of medical tourism in Indonesia also arise from reflecting on the perspective of state law neighbors, malpractice law in developing countries is weak, in Indonesia developments in the field of law are still not seen as a medium to change the order of people’s lives, medical tourism has cross-border litigation challenges. The health omnibus law as a national legal policy with the hope of achieving the goal of increasing the public health hierarchy in Indonesia was a challenge as well as the best opportunity in the future.